THE INFLUENCE OF KNOWLEDGE MANAGEMENT, SKILL, AND ATTITUDE ON EMPLOYEE PERFORMANCE - Hari Haji, Wachyu; Madiistriyatno, Harries; Widayati, C. Catur; Usman, Muhammad (Dinasti International Journal of Digital Business Management, 2021)
This research was to determine to influence Knowledge Management, Skill, and Attitude on Employee Performance. The Object of This Research Are Employees Who Work At PT Sun Life Syariah of Jakarta. This study was conducted on 35 respondents using a causal research design. This test's analysis technique is descriptive analysis and test instruments in the form of Validation and Reliability Tests with Version 3.0 of the Smart PLS (Partial Least Square) software. This study indicates that Knowledge Management has a positive effect on Employee Performance, and Skill has a positive effect on Employee Performance. Attitude has a positive effect on Employee Performance at PT Sun Life Syariah of Jakarta.